(untitled) (Altre Modernità, 2019)
In this essay the aim will be to reflect on the connection between colonization and feminization of the conquered territory, considering that in the asymmetric scheme of patriarchal domination, the territory or nation includes and incorporates gender, and gender is the sexual center of recognition in the construction of territorial and colonial identities. The analysis will refer to the intersections between sex and race, fundamental elements in the dichotomous domination-oppression mechanism, which is very strong in the colonial conquest phase. Colonialism emerges, therefore, as a masculine and phallocentric dimension, in which the female body becomes the center of production of the sexualization of the body inscribed within a social and public racial reproductive process. Feminism, especially the postcolonial theoretical horizon, has reflected on the connection of colonialism with racism and sexism, as elements aimed at a process of othering the ’other world’ with a connotation of permanence. In this perspective, the categorization of the "Third World" woman – as a sexually oppressed woman – is interpreted in a post-modern key of colonizing misogyny that has influences in today’s society, and this conceptualization is linked to the opposition between "western" feminism and "non-western" feminism.